2022
DOI: 10.3390/rs14112676
|View full text |Cite
|
Sign up to set email alerts
|

Automated Multi-Scale and Multivariate Geological Logging from Drill-Core Hyperspectral Data

Abstract: Hyperspectral drill-core scanning adds value to exploration campaigns by providing continuous, high-resolution mineralogical data over the length of entire boreholes. However, multivariate mineralogical data must be transformed into lithological domains such that it is compatible with interpolation techniques and be usable for geomodeling. Manual interpretation of multivariate drill-core data is a challenging, time-consuming and subjective task, and automated or semi-automated approaches are needed. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…HSI has been recently used in many industries including agriculture [31], astronomy [32], military [33], biosensors [34][35][36], remote sensing [37], dental imaging [38], environment monitoring [39], satellite photography [40], cancer detection [27,41], forestry monitoring [42], food security [43], natural resources surveying [44], vegetation observation [45], and geological mapping [46]. The visible-light hyperspectral imaging (VIS-HSI) developed in this study uses an aerial camera (DJI MAVIC MINI) image to convert the image into a hyperspectral image in the visible wavelength range of 380-780 nm and up to a spectral resolution of 1 nm.…”
Section: Hsi Algorithmmentioning
confidence: 99%
“…HSI has been recently used in many industries including agriculture [31], astronomy [32], military [33], biosensors [34][35][36], remote sensing [37], dental imaging [38], environment monitoring [39], satellite photography [40], cancer detection [27,41], forestry monitoring [42], food security [43], natural resources surveying [44], vegetation observation [45], and geological mapping [46]. The visible-light hyperspectral imaging (VIS-HSI) developed in this study uses an aerial camera (DJI MAVIC MINI) image to convert the image into a hyperspectral image in the visible wavelength range of 380-780 nm and up to a spectral resolution of 1 nm.…”
Section: Hsi Algorithmmentioning
confidence: 99%
“…Moreover, multispectral data can make up for the shortage of hyperspectral data to a certain extent, which can improve the spatial resolution by merging with panchromatic bands so as to enhance iron-stained alteration mineral anomalies and oxhydryl alteration anomalies more effectively, such as data from Landsat 8 OLI (OLI: multispectral sensor) and ASTER, among others. Combining multispectral data with hyperspectral data can provide more accurate alteration mineral identification [33][34][35][36]. Previous studies have shown that the extraction of iron-stained information usually base on the selection of only four bands for principal component analysis (PCA), which cannot fully reflect the variable features in the wave spectrum of iron-stained alteration minerals in detail [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In HSI, the data from the image are not only processed in the three visible colors but in the whole electromagnetic spectrum. HSI has been previously employed in agriculture [ 18 ], astronomy [ 19 ], military [ 20 ], biosensors [ 21 , 22 , 23 ], air pollution detection [ 24 , 25 ], remote sensing [ 26 ], dental imaging [ 27 ], environment monitoring [ 28 ], satellite photography [ 29 ], cancer detection [ 30 , 31 , 32 ], forestry monitoring [ 33 ], security [ 34 ], food security [ 35 ], natural resources surveying [ 36 ], vegetation observation [ 37 ], and geological mapping [ 38 ]. DR (DR) is one of the major complications of microvascular injury [ 39 ].…”
Section: Introductionmentioning
confidence: 99%